Perinatal growth and nutrition [ - Griffin, Ian J. (CRC Press, 2014)
"Preface Humans, like all mammals, have an inborn desire to nurture and suckle their young and the act of feeding is important for the bonding between mother and child. The birth of a critically ill preterm infant disrupts this, but for a mother, the use of her milk to feed her infant may be the most tangible role she has in the medical care of her critically sick child. Parents and caregivers see growth and feeding as important milestones first demonstrating increasing stability, then signaling the start of recovery, and finally showing readiness for discharge home. Despite our intuitive and emotional connection with growth, preterm infants grow poorly after birth and very commonly develop ex utero growth restriction (EUGR) or postnatal growth failure. There are many reasons for this including the associated medical conditions of prematurity, but inadequate nutrient intake plays a large part. This results both from technical difficulties in providing adequate nutrition, and from fears about the complications associated with doing so, including metabolic derangements such as hyperglycemia and hyperlipidemia, and diseases such as necrotizing enterocolitis. At the time of hospital discharge, many preterm infants are profoundly growth retarded, and their average weight is as little as 70% of that expected for their peers who were not born prematurely. Preterm infants show variable amounts of catchup growth after discharge, but typically remain smaller than the term-born peers throughout childhood and adolescence. This pattern of early growth restriction followed by variable amounts of catch-up growth has drawn parallels with the in utero growth restricted (IUGR), small-forgestational age, infant"--Provided by publisher.